The use of active strategies for teaching Latin syntax: a case study of a Brazilian classroom experience - Fortes, Fábio (PRINCIPIA, 2021)
In this paper, by showing a case study of a Latin teaching experience in Brazil, we discuss the relevance and usefulness of incorporating active strategies into the teaching of Latin syntax in a Brazilian university context. We mean here by active strategies any language practise consisting of producing language output, either orally or through writing, as a means of creating texts in this language to respond to classroom tasks. Our point is that through the development of task-based lessons with active strategies we may more easily engage students in their learning process and make more effective the learning of Latin syntax. We present a brief introductory discussion on what we consider to be how Latin is currently taught in Brazil, then we present an active teaching approach experience, and then we provide with some more conceptual arguments to justify such approach to this classical language.